THE CORRELATION BETWEEN STUDENT’S SELFCONFIDENCE AND SPEAKING ACHIEVEMENT - Sariakin; Yulsafli (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The self-confidence is frequently faced by the students in the classroom when the process of teaching and learning takes place. They are not confident, shy or uncomfortable if they made mistakes. They s are afraid of making errors in the classroom as they will be laughed at by their friends. The aim of the research is to investigate if whether there is any significant correlation between students’ self-confidence and speaking achievement. The population of this research is the students of Junior High School in Kota Banda Aceh. The total population of this study was 89 students. Meanwhile, the total sample of this study was 60. Choosing sample is done randomly. The needed data were collected through questionnaire and test. The data gotten were analyzed by using correlation product moment formula. The result of data analysis shows that t-score value is 4.08. It means there is any significance correlation between the students’ self-confidence and their speaking achievement because the value of t-score (4.08) is bigger than t table (2.00). Based on the result of the research, the students do not need to feel nervous and worry when speaking English in front of their friends, because it is a learning process. Thus, making mistake is very usual for those who start learning foreign language. Therefore, their selfconfidence can increase and it influences their success in speaking achievemen